Depiction of Nirutti on the Kakshasana wall of the Undeshwar Temple - Temples of India Project Team (Jio Institute, 2024)
A depiction of Nirutti is also present on the same Kakshasana (seat back) wall of the Undeshwar Temple. He is depicted standing with an erect phallus, holding a damaru (double-headed drum), a khetaka (shield), and a musala (pestle) in his hands. One of his hands is damaged. A broken animal can be observed at the bottom left. Nirutti's distinctive high-raised hairstyle is notable, and he is adorned with jewelry while wearing a lengthy garland.